2015
DOI: 10.1108/afr-04-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between financial and non-financial factors

Abstract: He has been involved in undergraduate and postgraduate programs for over seven years, and teaches courses such as security analysis, portfolio management, derivatives, international finance, and corporate finance. Dr Niblock is passionate about his research and is particularly interested in the carbon economy, socially responsible investment, informational efficiency of emerging markets and the risk-adjusted return performance of investment funds. He has also worked as a private client advisor in the stockbrok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
2
10
1
Order By: Relevance
“…and the financial health of the enterprise. The competencies and skills of management for the functioning of the company also proved to be important factors in the evaluation of the financial situation of agricultural enterprises in the study conducted by Purves et al [5]. The results of this research confirmed that important nonfinancial factors for the success of agricultural companies include the professional experience and knowledge of management and the appropriate level of its managerial qualifications.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…and the financial health of the enterprise. The competencies and skills of management for the functioning of the company also proved to be important factors in the evaluation of the financial situation of agricultural enterprises in the study conducted by Purves et al [5]. The results of this research confirmed that important nonfinancial factors for the success of agricultural companies include the professional experience and knowledge of management and the appropriate level of its managerial qualifications.…”
Section: Discussionsupporting
confidence: 71%
“…Financial difficulties cannot occur without reason and are often the result of changes in both the internal and external environment. According to Purves et al [5], for the rapidly changing situation in the economy of the agricultural sector, knowledge of the factors influencing the organizational success and solid survival of the companies is of extreme importance. Predicting the success or failure of agricultural holdings will become increasingly important as the growing population continuously increases the demand of food supplies.…”
Section: Introductionmentioning
confidence: 99%
“…Most investors use financial statements as a consideration before they decide where should invest their money. However, financial statements that used as an indicator in assessing the success or failure of an organization (in all sectors) do not seem to provide precise information about company performance in a certain period or series [7]. The financial ratio, financial performance, and organizational sustainability have been widely discussed as agricultural financial literature [7].…”
Section: Purposementioning
confidence: 99%
“…However, financial statements that used as an indicator in assessing the success or failure of an organization (in all sectors) do not seem to provide precise information about company performance in a certain period or series [7]. The financial ratio, financial performance, and organizational sustainability have been widely discussed as agricultural financial literature [7]. The historical financial performance of public-listed companies in America examines the median of profitability, liquidity, operating effectiveness, and market ratio [8].…”
Section: Purposementioning
confidence: 99%
“…Agribusiness is an economic industry of vital importance to Brazil because it contributes a significant share of job creation, positively supports the trade balance with the strength and magnitude of its exports, and substantially influences the composition of the Brazilian GDP (Wilkinson et al, 2015). Agricultural systems around the world are incrementally being dominated by vertically coordinated or integrated organizations (Gunderson et al, 2014;Purves et al, 2015). This is already a reality in developed countries and is being rapidly experienced in developing countries, especially in South America and Southeast Asia (Fao, 2005).…”
Section: Introductionmentioning
confidence: 99%